Pengaruh Ukuran Partikel Biosorben Terhadap Penyerapan Ion Logam Pb(II) Dari Biji Dan Kulit Lengkeng (Euphoria longan Lour) - Puja, Puja; Kurniawati, Desy (Periodic, 2019)
A study about the effect of biosorbent particle size on adsorption Pb ions from seeds and shell lengkeng (Euphoria longan lour) has been conducted. Shell and seeds lengkeng were activated with HNO3 and characterized by FTIR to analyze the mayor functional groups in biosorbent. The effect of seed and shell lengkeng (Euphoria longan lour) on the adsorption capacity of Pb (II) metal ions was carried out with variation 106 Î¼m, 150 Î¼m, 250 Î¼m, and 300 Î¼m. The results obtained from the particle size 106 Î¼m of seed and shell lengkeng have a greater adsorpsition of 25,626 mg/g dan 30,095 mg/g respectively. This study shows that the biosorbent particle size afffects the amount of adsorption of metal ions